Blood transfusions in dogs and cats from Portugal: a retrospective study - Dias, L; Vilhena, H; Carolino, N; Freire, A; Moura, M; Aleixo, R; Silvestre-Ferreira, AC; Duarte, S (Journal of the Hellenic Veterinary Medical Society, 2022)
Transfusion medicine has experienced a great evolution in recent years. Despite its generalization in veterinary medicine, the available information related to its clinical practice is scarce. This retrospective study aimed to characterize blood transfusions of whole blood and erythrocyte concentrates in companion animals performed in Portugal. In total, 116 animals were analysed, of which 59 dogs and 57 cats. Pre-transfusion blood typing was not performed on most animals (63.8%). In the animals in which pre-transfusion blood typing was performed, most cats (96.2%) were type A and most dogs (75.0%) were DEA1 positive. After the transfusions, most of the animals survived (77.2% cats and 64.4% dogs). The survival of cats after transfusion was significantly influenced by age, and in dogs by age and origin of blood, being that older animals had lower survival and animals transfused with blood components from a blood bank had a higher survival. Survival may have been influenced by other factors such as the animal's underlying disease. The mean pre-transfusion haematocrit in cats (11.8%) was lower than in dogs (16.7%). In dogs, the mean increase in haematocrit after transfusion was 9.0%, close to the recommended 10%, whereas in cats it was 6.5%. No transfusion reactions were recorded.